OPTIMALISASI PENGGUNAAN PETA TERMINAL DOMESTIK BERBASIS INTERNET OF THINGS DI BANDAR UDARA I GUSTI NGURAH RAI BALI - Titania Firda Yanto; Kukuh Tri Prasetyo; Kusno (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
In the industrial revolution 4.0, there were many developments of digital technology that makes it easier for various jobs, for example the barcode system to make it easier just by scanning, websites for online promotion places, and internet of things with many concepts that have begun to be developed and used for the automation process. Development of a map of the domestic terminal for the Ngurah Rai airport, which is based on the internet of things by creating a barcode that makes it easier to enter a website that contains a map of the terminal and what facilities are available at the domestic terminal of Ngurah Rai Airport. In addition, visitors can provide an assessment of existing facilities at the domestic terminal for future facility improvements. The facilities displayed are accompanied by a picture and description of the nearest location as well as designed in sequence so that passengers will not be confused in the boarding process. The method used in this research is Research and Development (R & D), with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model development procedure. The development of a map based on the internet of things by entering a barcode containing a website has been tested on passage online and can be used as a support tool in the boarding process at the domestic terminal at I Gusti Ngurah Rai Bali airport.